Neurons sensitive to pH in slices of the rat ventral medulla oblongata - Jarolimek, Wolfgang; Misgeld, Ulrich; Lux, Hans Dieter (Pflügers Archiv, 1990)
The effects of extracellular pH changes on neurons in slices of the rat ventral medulla oblongata were investigated by extracellular recording. Changes in discharge rate were correlated with pH changes in the tissue next to the recorded cell, as measured by H+-selective microelectrodes. pH was altered by varying the bicarbonate concentration ([HCO3−]) in the superfusion solution. In 136 out of 316 neurons, the number of spontaneous or electrically evoked discharges per unit time increased with decreasing pH and decreased with increasing pH. Changes of only 0.01-0.04 pH unit were effective in these pH-sensitive neurons. The response was transient; the discharge rate returned to the control value within a few minutes. The pH sensitivity persisted in the presence of 0.5 μM atropine, 20 μM bicuculline and after replacing Ca2+ by Mg2+ in the superfusion solution to reduce synaptic transmission. The response to the same pH decrease was stronger when increasing PCO2 than when reducing [HCO3−]0. The pH-induced response significantly increased during hypoxia. The results show that in the ventral medulla oblongata neurons exist that transiently respond to small decreases and increases of pH. The pH sensitivity is an intrinsic property of these neurons; it is not due to a synaptic mechanism but is modulated by PCO2 and PO2.